Menimbang Tafsir Al-Mishbah:Analisa Kritis Terhadap Tafsir Ayat Jilbab M. Quraish Shihab - Rohman, Abdul (Al Mudzakarah, 2024)
There is a diversity of interpretations regarding the Quranic verse on the jilbab. Among these interpretations, some are robust in terms of argumentation, while others appear biased and subjective. This article delves into Quraish Shihab's thoughts on the jilbab verse and critically analyzes them. This research is a type of library research using a descriptive analysis method, which describes the research findings based on a focused problem by critically analyzing them to produce objective results. The approach used is content analysis. The primary sources for this research are Tafsir Al-Mishbah and Jilbab Pakaian Wanita Muslimah. The research findings indicate: First, in Quraish Shihab's perspective, wearing the jilbab is not obligatory; its command is merely a recommendation and applies only during the time of Prophet Muhammad. Scholars also do not unanimously agree on the boundaries of a woman's aurat, and the jilbab sharia is a teaching that takes into account Arab societal traditions, making it not applicable to other nations that do not wear the jilbab. Second, Quraish Shihab's interpretation of the jilbab verse lacks a strong argumentative basis in Islamic studies. The wording of the command in the jilbab verse is still understood as an obligation and cannot be transformed into a mere recommendation because there is no evidence diverting it; scholars have unanimously agreed on the boundaries of a woman's aurat, which extends from the top of the head to the tips of the toes, excluding the face and the palms of the hands; the sharia of the jilbab remains applicable until the end of time, even though it was revealed under specific conditions and in a particular region, as Islam is a universal religion.